Law Enforcement of Right of Equality in Work for People with Disability: Evidence from Sleman, Indonesia - Susilo Andi Darma (Universitas Muhammadiyah Sidoarjo, 2016)
This research aims to understand the implementation of supervision law supervision toward Articles 5 and 14, and the law enforcement toward Article 28 of Law No.4 Year 1997 on People with Disability in Sleman Regency. Data are obtained through interviews and literature related to the problem. The results of this research show that the implementation toward article 5 and 14 are not yet effective and the law toward article 28 is not implemented yet in Sleman.